DIASPORA CHINEZĂ – REALITĂȚI ȘI PROVOCĂRI GLOBALE - Iordache, Ruxandra (Revista de Știinţe Politice şi Relaţii Internaţionale, 2023)
The Chinese Diaspora represents a very interesting and complex demographic, sociological and geopolitical issue. Even if one could say that the main reason of Chinese people migrating from China is economic, sometimes in terms of survival needs, this phenomenon reaches additional but very important features, especially in the context of the peculiarities of the Chinese political regime. A communist country has a very numerous Diaspora, and despite the political opposition to the regime that some Chinese migrants manifest, the Diaspora is converted into a force strengthening the country. The Chinese may live far away, but the ties with their country remain very strong. The present article investigates some dimensions of this phenomenon, the vectors that made from the first modest Chinese migrants of the recent past, the global challenge that nowadays has all kind of implications for the destination countries and societies.